The Design and Development of iInvest Application - rahim, aiman; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2023)
iINVEST application is proposed to provide support, mostly for youth or any other amateur investors, and equip them with proper knowledge and skills in investment endeavor regardless of their background where newcomers in this commercial and trading industry usually have major issues with high-risk investments and lose their capital. This application is an online mobile learning application for youth below 40 years, who are into investment in real estate, shariah compliance forex and shariah compliance coin mining. This application is proposed to be developed using evolutionary prototyping model as the phase will be iterated until the target user requirement has been achieve. One of the application's key advantages is that the user could attempt to make a mock investment on the chart module against other users who are actually using real money. Lastly, system prototype is developed to make sure that the application fulfills all the of requirements.